Changing Evidentiary Rules to the Detriment of the Accused? The Ruto and Sang Decision of the ICC Appeals Chamber (Polish Yearbook of International Law, 2017)
The main topic of this article is retroactive application of procedural criminal law. In this text the question will be posed – and answered – whether the application of a new procedural provision that entered into force in the course of an ongoing proceeding should in that proceeding be considered as retroactive and in what scope or/and under what conditions can such retroactivity be allowed for. As will be shown the solutions in national jurisdictions diﬀer according to the common law – continental law states divide. This problem will be discussed in the light of a decision in the ICC Ruto and Sang case. In this case the ICC Appeals Chamber had to answer several questions pertaining to the temporal application of new procedural provisions. Firstly, the Chamber had to decide whether a general ban on the retroactive application of substantive law should also apply to procedural criminal law. Secondly, the ICC Appeals Chamber had to analyze the criteria according to which it would evaluate whether the change of rules of criminal procedure in the course of an ongoing trial was to be considered as having a retroactive eﬀect, and whether the change in the rules of admission of evidence could be considered detrimental to the accused. Tirdly, it will be shown that the ICC Appeals Chamber has chosen the common law concept of “due process rights” rather than the idea of “intertemporal rules” known from the continental doctrine, and why it chose to do so.